The Social Events and the Development of Arabic Language in the Early Period of Islam - Wildana Wargadinata; Iffat Maimunah (Buletin Al-Turas, 2021)
This paper discussed the social phenomena that occurred during the birth of Islam and its influence on the revolution process in developing the Arabic language. The study was a qualitative research with a descriptive design relying on documents and literature of al-Mujtama'at al-Islamiyah as the primary reference source. This paper showed the social events that accompanied the birth of Islam had an impact and influence on the growth and development of the Arabic language. The social events during the early period of Islam were a great momentum for the revelation of the Qur'an, the entry of Islamic teachings into the Arab ignorant society. The establishment of social interaction relations between Arab and Islamic communities became a powerful event in forming the Arabic language. Thus, the early period of the birth of Islam was a time of transformation in standard Arabic. The events and social phenomena that occurred during the early period of Islam also had implications for the growth process of knowledge originating from Islam. The Arab community had made standard Arabic the primary language in delivering Islamic teachings and the development of science. This paper suggested the need for a further study of the development of the Arabic language viewed from the historical aspect.